Poetics Of Sabir Saikali’s Poetry - Jumanov Bektosh (International Journal on Integrated Education, 2022)
The 17th and 18th centuries are significant in the history of Uzbek literary studies because they promoted the traditions established up to that point, added new literary works to the canon, and fostered the development of folk creative ideas. All forms of creativity continued to flourish during this time, and historiography, music science, architecture, geography, and other disciplines left their imprints on Uzbek culture and art history.